Act One. Comfort the Waste Places, Defend the Violated Earth. An Ecofeminist Reading of Isaiah 51:1-52:6 and Tracy Chapman's "The Rape of the World". Act One. Comfort the Waste Places, Defend the Violated Earth. - Angela Sue Sawyer (Journal for Religion, Film and Media, 2020)
This paper compares the personification of Zion in Isaiah 51:1-52:6 as a mother and daughter with Tracy Chapman's 1995 song "The rape of the world" where the earth is portrayed as mother. I will explore the use of rape imagery and how both pieces portray the negative effects of human activity on the earth, whether by commercial activity or war. The environmental impact of the desolation of the earth during the Babylonian exile depicted in Isaiah and its portrayal via gendered images is viewed through the lens of ecofeminist criticism. The earth itself has a voice in both Chapman's and Isaiah's words.